Konsep Invasi Ruang Eventual: Fleksibilitas Penggunaan Ruang pada Perancangan Rusunawa - Wastara, Joshua Gama; Hayati, Arina (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Spatial invasion is a subjective expression of low-income communities in the riverbank areas. This lifestyle is one of the expressions of society to meet the lack of spatial space in residential areas, especially in riverbank areas. The previous study stated several things, the invasion of the lifestyle of the riverside community has occurred especially when the settlements were divided spatially. Besides, the precedent for the rusunawa in Surabaya shows its design by providing spaces that connected spaces, units, and buildings, which are usually invaded by the inhabitants for domestic and social activities. Qualitative studies were obtained to find the configuration of spatial invasion through activity observations and in-depth interviews with several participants living in riverbank settlements. This study analyses whether the use of space in the flat can be designed under similar activities and the use of spatial intervention in the kampung settlement, in this context near the river border. The results showed that there were similarities in the use of public spaces in residential areas and rusunawa, namely eventual space invasion that is used as the design concept. Shared space for community activities in the settlements can be adopted and provided in flat design with the support of several architectural elements. These expressions are then simulated into several concept illustrations of a flat design proposal with several required conditions. The result proposes several potentials of space in the flat that can be used for domestic and social interests.